Political socialization of the youth under digitalization: A research question - A. A. Svistunov (RUDN journal of Sociology, 2025)
The article considers the urgent problem of political socialization of the youth under the rapid development of digital technologies: contemporary approaches to the study of value priorities of the youth and various concepts of socialization under digitalization of political socialization; interpretations of the “digital society” and the request for the choice of such a concept that would reflect the real state of affairs and contribute to a more stable and independent political development; key aspects of digital socialization as the basis for a more in-depth study of the youth political socialization. The article consists of three parts: in the first part, the author briefly presents the sociological interpretation of socialization of the youth as a special social-demographic group; the second part explains the “status” of digitalization as a new socialization factor (and even an alternative to traditional agents of socialization) at the microand macro-levels due to the complex interweaving of its obvious advantages and significant risks; the third part focuses on the key features, mechanisms and consequences of the impact of digitalization on political socialization (in the narrow and broader senses of this concept) in its mass manifestations. The author comes to the conclusion that today political socialization is an interdisciplinary object of scientific interest, and its study should take into account the formation of a new social reality under digitalization at the technological and social-symbolic levels. Thus, we need an updated concept of the youth digital political socialization as a theoretical-methodological basis for further fundamental and applied research. Such a concept would help to ensure stable political development by adapting younger generations to the challenges determined by dynamic changes in the political sphere.